LG in India (A) : entry into an emerging economy - Salwan, Prashant (SAGE Knowledge. Cases., 2011)
LG, a large multinational Korean company, decided to enter India employing a green field entry strategy as a wholly owned subsidiary in 1997. This case helps students analyse the reasons behind this decision, describing the external and internal environment which was prevalent at the time of entry. The case provides details of the various consumer electronics markets until 2005, and the key potential success factors identified by the then MD of LG India Ltd, Mr. Kim.